Erosion characteristics of molten aluminum droplets bouncing off solid walls in solid rocket motors. (December 2022) - Fu, Yu; Hu, Ying; Hu, Chunbo; Li, Fengchao; Li, Chao
Abstract: Based on the microscopic process of particles eroding the solid wall in the combustion chamber of solid rocket motors, the erosion mechanism of aluminum droplets in the process of vertical impact on solid walls is analyzed. Firstly, a method for measuring the impact force of the high-temperature molten-metal droplet is proposed on the basis of the pneumatic droplet generation method and piezoelectric force measurement technology. Then, the impact force of aluminum droplets with varing diameters and velocities is systematically studied. Additionally, the time-domain process of impact force in the rebound process of the aluminum droplets is obtained, and the coupling mechanism between the impact force and deformation process is analyzed and obtained. Then, based on the VOF interface tracking and the PLIC reconstruction method, the numerical model of the aluminum droplet impact force is established. On this basis, direct numerical simulations on the erosion effect of aluminum droplets on solid walls are carried out. Combining with the experimental results, the generation mechanism of the impact force and the influence mechanism of various parameters on the impact force during the rebound process of aluminum droplets are explored in depth. Ultimately, a semi-empirical prediction formula for the maximum value and duration of the impact force in the rebound process of the aluminum droplets is developed. Our research work can improve the cognition of the mechanism of the insulation materials in the combustion chamber of solid rocket motors, and thus expand the knowledge of engine structure design work. Highlights: A measurement method of high-temperature molten metal droplet impact force. Systematic experimental research on the impact force of aluminum droplets. The evolution mechanism of the impact force and the influence mechanism of various parameters. A semi-empirical formula for the impact force of aluminum droplets.